Numerical solution of dual-phase-lagging heat conduction model for analyzing overshooting phenomenon - Mishra T.N.; Sarkar S.; Rai K.N. (My University, 2025)
The overshooting phenomenon based on one dimensional dual-phase-lagging heat conduction model, has been studied by numerical technique. The effect of Fourier number and B=(τT/2τq on overshooting phenomenon have been observed. The stability of the numerical scheme has been discussed and observed that the solution is unconditionally stable. The whole analysis is presented in dimensionless form. © 2014 Elsevier Inc. All rights reserved.